Adnexal masses requiring reoperation in women with previous hysterectomy with or without adnexectomy. (May 2016) - Shiber, Linda-Dalal J.; Gregory, Emily J.; Gaskins, Jeremy T.; Biscette, Shan M.
Abstract: Objectives: To characterize the etiologies of adnexal masses requiring reoperation in women with prior hysterectomy and to compare incidence and pathology of these masses based upon whether total, partial or no adnexectomy was performed at time of hysterectomy. In addition, the average time interval between hysterectomy and reoperation for a pelvic mass is ascertained. Study design: A single-institution, retrospective review spanning 10 years. Using pertinent ICD-9 and CPT codes, women with a history of hysterectomy who underwent a subsequent surgery for an adnexal or pelvic mass were identified. Results: Over ten years, 250 women returned for gynecologic surgery due to a pelvic mass after prior hysterectomy. Most had undergone hysterectomy only (76%). 64.8% of these women had masses of ovarian origin, 12.4% were tubal in origin, 20% of masses involved both the ovary and tube and a small proportion arose from non-gynecologic processes. 18% of these women had a malignancy; 80% were ovarian and 6.7% originated from the fallopian tube. Patients having had a prior hysterectomy and bilateral salpingectomy returned soonest ( p < 0.0001) and patients with malignant masses returned after the longest time intervals (HR 0.41, p < 0.0001). Conclusions: The majority of adnexal masses requiring reoperation after hysterectomy are gynecologic in origin, benign, and arise from the ovary. Women returning with malignant masses after hysterectomy present after longer time intervals.